Fatal neonatal nemaline myopathy: a case report. Issue 9 (September 1983) - Tsujihata, M; Shimomura, C; Yoshimura, T; Sato, A; Ogawa, T; Tsuji, Y; Nagataki, S; Matsuo, T
Abstract : A fatal neonatal nemaline myopathy in a Japanese girl was described. The patient was hypotonic at birth and failed to establish effective respiration. Rod-like structures were observed within a variety of skeletal muscles, particularly in the diaphragm. This is the first case of fatal neonatal nemaline myopathy in which many satellite cells were observed.